ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TELLER TERBAIK DENGAN MENGGUNAKAN METODE PROFILE MATCHING PADA PT. BANK CENTRAL ASIA, TBK - Aileen, Aileen; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2019)
In an effort to develop tellers, PT. Bank Central Asia chooses the best teller every year as a form to provide work motivation to tellers. The best teller selection system at PT. Bank Central Asia, Tbk the Jambi has been carried out manually by direct observation from the section head and knowledge test which requires a long time and is not objective, and has not been well documented so that it requires an information system that can help in the selection process of the teller in the selection process and documentation process. In this case, the appropriate information system is a decision support system using the Profile Matching method. Profile Matching method is very appropriate to use because this method measures the ability of the teller according to the target profile that has been. The system modeling tool used is UML (Unified Modeling Language). This study produced a prototype decision support system for selecting the best tellers that can be implemented in accordance with existing needs, especially in the selection of the best tellers at PT. Bank Central Asia, Tbk Jambi so that it will shorten the time needed and the electoral process will take place objectively.